TEACHING PRESCHOOL CHILDREN CREATIVE THINKING USING INNOVATIVE PEDAGOGICAL TECHNOLOGIES (Academicia Globe: Inderscience Research, 2023)
This article provided feedback on the concept and essence of creativity, the formation of creativity in preschool children.